2022
DOI: 10.3389/fpsyg.2022.902782
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing customer satisfaction with chatbots: The influence of communication styles and consumer attachment anxiety

Abstract: Chatbots are increasingly occupying the online retailing landscape, and the volume of consumer-chatbot service interactions is exploding. Even so, it still remains unclear how chatbots should communicate with consumers to ensure positive customer service experiences and, in particular, to improve their satisfaction. A fundamental decision in this regard is the choice of a communication style, specifically, whether a social-oriented or a task-oriented communication style should be best used for chatbots. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…First, we enrich the adapted theory of relational personalization with findings from our systematic literature review on conversation styles of conversational AI in customer service. We then draw from the findings on individual conversation styles, such as small talk (Xu et al. , 2022) and empathy (Han et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…First, we enrich the adapted theory of relational personalization with findings from our systematic literature review on conversation styles of conversational AI in customer service. We then draw from the findings on individual conversation styles, such as small talk (Xu et al. , 2022) and empathy (Han et al.…”
Section: Discussionmentioning
confidence: 99%
“…The systematic literature review further showed that small talk as a conversation style can create a social presence and is associated with desirable outcomes in customer service conversations (Nguyen et al ., 2022). Similarly, Xu et al. (2022) have shown that social-oriented communication (vs task-oriented), such as customary greetings, social praise, or well-wishing boosts customer satisfaction.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Attributes of competence include capability, intelligence and efficiency (Aaker et al , 2010). When an e-service agent interacts with customers, these two dimensions provide useful information about how customers respond to different communications or interactions (Xu et al , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%